DISTRIBUTION OF CVPDr GENE AMONG SOME CITRUS PLANTS IN BALI - Wirawan, I Gede Putu (International Journal of Biosciences and Biotechnology; Vol 3 No 2 (2016), 2016)
Citrus Vein Phloem Degeneration (CVPD) is the main disease of citrus plant caused by a Gram negativebacteria, Candidatus Liberobacter asiaticus. The disease is also called citrus greening disease or recentlycalled citrus huanglongbing. The CVPDr gene was firstly found in Triphacia trifoliata a citrus relativeplant which considered to be resistant to CVPD disease. The distribution of the gene among the citrusrelative plants in Bali were studied. The result of this study so far, CVPDr gene were found in theseedless lime (Citrus aurantiifolia) and Triphacia trifoliata which are known as a resistant or tolerant toCVPD disease, however, Citrus maxima, Citrus nobilis, Citrus reticulate, and Citrus amblycarpa are allsensitive plants but their harboring the CVPDr gene. This result indicated that CVPDr gene was not givea resistant to the disease in these plants. This results suggested that other/s gene is needed to give aresistant or tolerant in these plants.
Keywords: CVPD gene, citrus plants,